Memória e Transformação da Quinta do Vilarinho - Filipe Tavares Ventura Barros Nunes (2023)
The main objective of this dissertation is the study, the analysis and the development of a rehabilitation project for a farm named "Quinta do Vilarinho" located in a place that goes by the same name "Vilarinho" which in turn is located in the region of Sever do Vouga. The title "Memória e Transformação da Quinta do Vilarinho" was born of a special connection with the place itself given that it belongs to my family for several generations and i always had a close relationship with it since being a kid, imagining what it could be in the future. My proposal has two main objectives: to enhance the House for family usage and to rehabilitate the ruins with the aim of making them suited for touristic purposes which would make the farm sustainable as a whole and it would give life to Vilarinho once more. This dissertation is divided into three chapters where i explore the different themes that were essential for the development of the project. I hope that, with this work, i can contribute with my own vision for the place, respecting its ancestors and its memory.